SYNTHESIS OF ENCAPSULATED CHROMOLAENA ODORATA LEAF EXTRACT IN CHITOSAN NANOPARTICLE BY USING IONIC GELATION METHOD AND ITS ANTIOXIDANT ACTIVITY - IDACAHYATI, KENI; WULANDARI, WINDA TRISNA; INDRA, FIRMAN GUSTAMAN AND INDRA (International Journal of Applied Pharmaceutics, 2021)
Objective: The aim of this study was to determine the antioxidant activity of Chromolaena odorata. Methods: Encapsulation of Chromolaena odorata leaf extract by nano chitosan was synthesized by using chitosan and NaTPP as the crosslinking agent. The antioxidant activity was conducted by using the DPPH method. Results: Nanoparticles of Chromolaena odorata leaf extract has an average diameter of 675±218 nm and+23.4±7.14 mV of zeta potential. The antioxidant activity of its extract was 0.86 ppm, while its nanoparticle has the better antioxidant activity of 0.21 ppm. Conclusion: Nanoparticles of Chromolaena odorata have very strong antioxidant activity and the potential to be external antioxidants.